Rear Admiral Richard E. Byrd's Plane, 1936 - Hutchison, Ralph Raymond (Manuscripts, Archives, and Special Collections, Washington State University Libraries: https://libraries.wsu.edu/masc, 1936)
An airplane sits at the Pullman airport. The side reads Byrd Antarctic Expedition